Canals and Communities : Small-Scale Irrigation Systems - Mabry, Jonathan B., 1961- (Book collections on Project MUSE., 1996)
Includes material on irrigation in Mexico, Somalia, Morocco, the Andes, Bali, Cape Verde, Iran, and Sri Lanka.